Examining the Sentencing of American Indian Women in U.S. Federal District Courts - Kramer, Kelsey L. (Crime & delinquency, 2024)
Prior sentencing research has examined the treatment of White, Black, and Hispanic defendants; however, little attention has been paid towards other racial/ethnic groups, like American Indian defendants. Moreover, a majority of sentencing research has focused men’s outcomes, disregarding the treatment and outcomes of women. Therefore, this paper examines the outcomes of American Indian women in federal district courts using United States Sentencing Commission (USSC) data from FY2015 to FY2019. We situate our research within an intersectional framework and use the chivalry, evil women, and focal concerns perspectives to understand the sentencing outcomes of American Indian women. Our results indicate that American Indian women are similarly disadvantaged at the incarceration, and sentence length decisions as other racial/ethnic groups.